2020
DOI: 10.3390/nano10101968
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SiO2 Particles in Polyethylene Textile Membrane for Indoor Personal Heating

Abstract: Keeping the human body in a thermal comfort state inside a room has become a challenge in recent years. While the most common strategy is to heat buildings, it requires a lot of energy. Reducing this energy consumption will have positive impacts, both economically and environmentally. We propose here to act directly on the personal thermal heating of the human body, by modulating the absorption and transmission properties of a synthetic polymer membrane in the mid-infrared (MIR). We show numerically that 5% Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, there is no strict requirement on the size of the SiO 2 particles in this material design. With a suitable particle filling concentration and film thickness, random sized particles are sufficient to enable high mid-infrared emissivity, , which have a lower cost to fabricate, unlike the previous study where a specified size of the SiO 2 particles is needed …”
mentioning
confidence: 96%
“…Furthermore, there is no strict requirement on the size of the SiO 2 particles in this material design. With a suitable particle filling concentration and film thickness, random sized particles are sufficient to enable high mid-infrared emissivity, , which have a lower cost to fabricate, unlike the previous study where a specified size of the SiO 2 particles is needed …”
mentioning
confidence: 96%
“…In some cases, to avoid time consuming calculations, we used the generalized transfer-matrix method to calculate R and T. [29] In this paper, all simulations have been performed for an electromagnetic plane wave at normal incidence. The effect of the incident angle has been considered in a previous work [19] resulting in a small variation of the mean optical response for angles less than 40°. As the incidence is normal and the surface of the structure is flat, the wave polarization is not an issue.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Of course, PE is also well known in the industrial field for many applications [ 23 ] and in particular a form derived from PE, the nanoporous PE (nanoPE) which has been used for textile applications in recent years. [ 8,15,20,24 ] The optical properties of the nanoPE are similar to the PE in the infrared range [ 8,19 ] offering in addition more breathability and flexibility due to the presence of the nanopores. Therefore, all results and demonstration presented in this work are valid in the case of nanoPE membranes.…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…65 A sandwich membrane consisted of MnO 2 and Cu nanowires on the skin side and cellulose @ LDH membrane on the outside can reflect the IR radiation of the body. 71 Boutghatin et al 72 showed that by inserting 5% SiO 2 submicron particles in PE membrane, the membrane's radiative heating increases, which reduces the 1.1 C set point. A polymer photonic membrane with air holes can modulate the optical spectrum in the MIR range and thermoregulate the human body microclimate.…”
Section: Radiative Heating Membranesmentioning
confidence: 99%